Efeitos de baixa dose de dexmedetomidina no ponto de acupuntura Yintang comparado a outras vias de administração em gatos - Fernandes, Michelly Ferreira (2023)
Chemical restraint is often required in feline veterinary practice to improve safety and facilitate handling when performing minor procedures on these animals without general anesthesia. One of the possibilities studied is the use of the sedative and anxiolytic effects of the stimulation of some acupuncture points associated with the administration of tranquilizing and/or sedative drugs, through pharmacopuncture. As the use of pharmacopuncture with dexmedetomidine in dogs and cats has determined variable results, the aim of this study was to compare the sedative and cardiorespiratory effects of dexmedetomidine in different routes of administration. Eight cats were sedated with 3mcg/kg of dexmedetomidine injected subcutaneously at the Yintang acupuncture point, intramuscularly, subcutaneously at the cervical region, and saline at the Yintang acupuncture point. Assessments of sedation and physiological variables were performed 10 minutes before application, and continued at regular intervals of 10 minutes until completing 60 minutes of administration or while the effect of the sedative lasted. The duration and quality of sedation were assessed using two scales proposed by Selmi et al. (2003) and Granholm et al. (2006). Heart and respiratory rates, arterial, systolic, diastolic and mean pressures were recorded at all times, however, body temperature, measured rectally, was recorded only at baseline and final evaluation. The duration and intensity of sedation fluctuated according to the route of administration, with no important significant changes or trends of oscillations on the cardiorespiratory variables measured. Both the acupoint (YT group) and IM routes had similar times and degrees, with persistence of sedation for at least 60 minutes, higher degrees of sedation between T20 and T50, and peaks of drug action between T30 and T40 in most parameters evaluated. The SC route, on the other hand, presented reduced degrees and sedation time compared to the other treatments with dexmedetomidine and similar to the PLA treatment.